47Calcium absorption in parenchymatous and biliary liver disease. Issue 12 (December 1971) - Whelton, Michael J.; Kehayoglou, A. K.; Agnew, J. E.; Turnberg, L. A.; Sherlock, Sheila
Abstract : As measured by whole body retention of isotopic calcium given in milk, absorption of calcium was impaired in 10 patients with chronic parenchymal non-biliary liver disease who were icteric. Mean absorption was normal in 15 patients with parenchymal liver disease who were anicteric although some individual patients absorbed less than any of the controls. Depressed absorption of calcium was seen in 10 patients with primary biliary cirrhosis and seven patients with intra- or extra-hepatic biliary obstructive disease. The most likely cause for this malabsorption is reduced bile salt secretion into the intestinal lumen which impairs vitamin D and fat absorption. The finding that parenteral vitamin D increased calcium absorption to normal levels in five patients with primary biliary cirrhosis suggests that deficiency of this vitamin is a major and correctable factor leading to calcium malabsorption in such patients. Precipitation of calcium salts by excess intraluminal fat appears to be a further possible factor reducing calcium absorption in these patients. These findings emphasize the importance of parenteral vitamin D therapy in patients with chronic obstructive biliary diseases. They also suggest that certain patients with chronic parenchymatous liver disease, particularly those who are icteric, may also occasionally require therapy with vitamin D.